Determinants of unmet need for family planning in Gambia & Mozambique: implications for women's health - Sanni Yaya; Dina Idriss-Wheeler; Olalekan A. Uthman; Ghose Bishwajit (BMC, 2021)
Abstract Background In low-middle-income countries, unmet need for family planning (FP) constitutes a major challenge for prevention of unintended pregnancies and associated health and psychological morbidities for women. The factors associated with unmet need for family planning have been studied for several countries in sub-Saharan Africa, but not much is known about the situation in Gambia and Mozambique. The purpose of this study was to perform a comparative analysis of the prevalence of unmet need for FP, and its sociodemographic correlates in Gambia and Mozambique to better inform FP policies and programs aimed at reducing associated negative health outcomes for women and their families. Methods In this analysis we used nationally representative data from Demographic and Health Surveys in Gambia (2013) and Mozambique (2011). Sample population were 23,978 women (n = 10,037 for Gambia and 13,745 for Mozambique) aged 15-49 years. Women who want to stop or delay childbearing but were not using any contraceptive method were considered to have unmet need for FP. Association between unmet need for FP and the explanatory variables was measured using binary logistic regression models Results Prevalence of unmet need for FP was 17.86% and 20.79% for Gambia and Mozambique, respectively. Having employment in professional/technical/managerial position showed an inverse association with unmet need both in Gambia [OR = 0.843, 95% CI 0.730, 0.974] and Mozambique [OR = 0.886, 95% CI 0.786, 0.999]. Education and household wealth level did not show any significant association with unmet need. The only positive association was observed for rural [OR = 1.213, 95% CI 1.022, 1.441] women in the richer households in Gambia. Having access to electronic media [OR = 0.698, 95% CI 0.582, 0.835] showed a negative effect on having unmet need in Mozambique. Women from female headed households in Gambia [OR = 0.780, 95% CI 0.617, 0.986] and Mozambique [OR = 0.865, 95% CI 0.768, 0.973] had lower odds of unmet need for FP. Conclusion The situation of unmet need for FP in Gambia and Mozambique was better than the Sub-Saharan African average (25%). Nonetheless, there is room for improvement in both countries. Significant assocations with lower unmet need for family planning and women's occupational status (more education & higher skilled employment), access to mass media communication, and female-headed households provide possible areas for intervention for improved FP opportunities in the region.